Perencanaan Remote Control dan Monitoring Apron Flood Light Selatan Berbasis Programmable Logic Control (PLC) di Bandar Udara I Gusti Ngurah Rai - Bali - Megansa, Kevin Sari; Bunahri, Rifqi Raza; Nugrahayani, Tiara; Kona, Musri (SKY EAST: Education of Aviation Science and Technology, 2023)
I Gusti Ngurah Rai International Airport has 8 ADP and 52 apron flood light poles equipped with LED lights. The travel distance from the Main Power House (MPH) to the flood light apron is ± 1,900 meter. Currently, flood lights operate automatically via a timer. All flood lights in the apron area will turn on at 18.00 WITA, then turn off at 06.00 WITA. Thus, the flood lights in the apron area or in the parking lot will remain on from 18.00 WITA to 06.00 WITA, even if there are no planes parked. The apron flood light at I Gusti Ngurah Rai Airport only uses a timer to control it and turn it off. The disadvantage of using a timer is that if the sun sets or rises earlier than the specified time, the apron flood light will not be able to turn on at that time. This research uses qualitative methods to obtain results. With this control and monitoring system, electricians and AMC can monitor lights via computer remotely without having to go to the field. 2. The existence of this control and supervision system can speed up the process of repairing and analyzing disturbances that occur as well as increasing the comfort of airport services for lighting aircraft when they are in Remain Over Night (RON) conditions at the parking stand.